The impact of exponentially varying viscosity on magnetized tangent hyperbolic nanofluid over a nonlinear stretching sheet with PHF and PMF conditions - Ghazy, Mohamed Magdy; Mekheimer, Khalid Saad; Abo-Elkhair, Rabea Elshennawy; Megahed, Ahmed Mostafa (Teknomekanik, 2025)
This article aims to explore the characteristics of tangent hyperbolic nanofluid flow over a nonlinear exponentially stretching sheet with suction or injection embedded in a Darcy porous medium. We consider a non-Newtonian magnetohydrodynamic fluid with prescribed surface temperature and temperature-dependent viscosity, relevant to applications in aerospace, automotive and marine engineering, electronic cooling, solar-energy systems, and filtration. Given its fundamental importance, the study of prescribed exponential order heat flux (PHF) and prescribed mass flux (PMF) of hyperbolic tangent nanofluid became a key in research aimed at improving the efficiency and performance of these systems. The partial differential equations are converted into ODES by using transformation procedure. The system of transformed equations is numerically solved by Chebyshev spectral method. Graphical results illustrate the impact of key parameters on concentration, velocity, and temperature profiles, while tabulated data report the local Nusselt number, Sherwood number, and skin friction coefficient. Our results show that increasing both the power-law index and the variable-viscosity parameter reduces the fluid’s velocity while elevating its temperature and concentration. The comparative analysis confirms a high degree of agreement with previous studies. This research holds significant importance as it focuses on the extensive utilization of tangent hyperbolic nanofluids in cooling electronic components that produce substantial heat during their operation.